2011
DOI: 10.1371/journal.pone.0021976
|View full text |Cite
|
Sign up to set email alerts
|

Graph Theoretical Analysis of Functional Brain Networks: Test-Retest Evaluation on Short- and Long-Term Resting-State Functional MRI Data

Abstract: Graph-based computational network analysis has proven a powerful tool to quantitatively characterize functional architectures of the brain. However, the test-retest (TRT) reliability of graph metrics of functional networks has not been systematically examined. Here, we investigated TRT reliability of topological metrics of functional brain networks derived from resting-state functional magnetic resonance imaging data. Specifically, we evaluated both short-term (<1 hour apart) and long-term (>5 months apart) TR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
368
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 353 publications
(400 citation statements)
references
References 73 publications
29
368
3
Order By: Relevance
“…We chose nodal degree because the number of connections or edges a node has to other nodes has been demonstrated to be a reliable index of network integrity. 43 We identified 17 brain regions whose nodal degree was negatively correlated with HAMD-24 scores. They included the prefrontal cortex, parietal cortex (right precentral gyrus and left precuneus gyrus), temporal cortex (bilateral fusiform and left superior temporal gyrus), the limbic system (bilateral posterior cingulum) and related brain areas (bilateral insula) and the basal ganglia (bilateral caudate and right putamen).…”
Section: Discussionmentioning
confidence: 99%
“…We chose nodal degree because the number of connections or edges a node has to other nodes has been demonstrated to be a reliable index of network integrity. 43 We identified 17 brain regions whose nodal degree was negatively correlated with HAMD-24 scores. They included the prefrontal cortex, parietal cortex (right precentral gyrus and left precuneus gyrus), temporal cortex (bilateral fusiform and left superior temporal gyrus), the limbic system (bilateral posterior cingulum) and related brain areas (bilateral insula) and the basal ganglia (bilateral caudate and right putamen).…”
Section: Discussionmentioning
confidence: 99%
“…Second, one has to note that present graph theoretical analysis provides only a macroscopic view on brain functional organization and previous research has shown that how brain graphs are constructed, compared, and normalized to reference models may change results considerably (Zalesky et al, 2010;Wang et al, 2011). To control for a methodological bias, we compared metrics across different brain parcellations and performed analyses on degree-preserved graph partitions.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…In the present study, we follow the same criteria since most of the previous publications in the neuroscience field have utilized the same or very similar criteria. 6,[8][9][10]15,18,19 Note that different applications may vary the ICC range to a large extent based on specific needs and definitions given by individual clinical applications. 20,21 In general, using ICC ¼ 0.40 as the floor of an acceptable range for the reliability of measurements is still reasonable as most fMRI results have ICC values of 0.33 to 0.66, 22 which are commonly considered reliable.…”
Section: Icc Criteria To Assess Reliability Of Measurementsmentioning
confidence: 99%